Overexpression of Caveolin‐1 Is Sufficient to Phenocopy the Behavior of a Disease‐Associated Mutant. (7th April 2013) - Hanson, Caroline A.; Drake, Kimberly R.; Baird, Michelle A.; Han, Bing; Kraft, Lewis J.; Davidson, Michael W.; Kenworthy, Anne K.
<x xml:space="preserve">Abstract</x> Mutations and alterations in caveolin‐1 expression levels have been linked to a number of human diseases. How misregulation of caveolin‐1 contributes to disease is not fully understood, but has been proposed to involve the intracellular accumulation of mutant forms of the protein. To better understand the molecular basis for trafficking defects that trap caveolin‐1 intracellularly, we compared the properties of a GFP‐tagged version of caveolin‐1 P132L, a mutant form of caveolin‐1 previously linked to breast cancer, with wild‐type caveolin‐1. Unexpectedly, wild‐type caveolin‐1‐GFP also accumulated intracellularly, leading us to examine the mechanisms underlying the abnormal localization of the wild type and mutant protein in more detail. We show that both the nature of the tag and cellular context impact the subcellular distribution of caveolin‐1, demonstrate that even the wild‐type form of caveolin‐1 can function as a dominant negative under some conditions, and identify specific conformation changes associated with incorrectly targeted forms of the protein. In addition, we find intracellular caveolin‐1 is phosphorylated on Tyr14, but phosphorylation is not required for mistrafficking of the protein. These findings identify novel properties of mistargeted forms of caveolin‐1 and raise the possibility that common trafficking defects underlie diseases associated with overexpression and mutations in caveolin‐1.